Electrochemical and Electroconductive Behavior of Silk Fibroin Electrospun Membrane Coated with Gold or Silver Nanoparticles - Wilson Agudelo; Yuliet Montoya; Alejandra Garcia-Garcia; Adriana Restrepo-Osorio; John Bustamante (Membranes, 2022)
The surface modification of materials obtained from natural polymers, such as silk fibroin with metal nanoparticles that exhibit intrinsic electrical characteristics, allows the obtaining of biocomposite materials capable of favoring the propagation and conduction of electrical impulses, acting as communicating structures in electrically isolated areas. On that basis, this investigation determined the electrochemical and electroconductive behavior through electrochemical impedance spectroscopy of a silk fibroin electrospun membrane from silk fibrous waste functionalized with gold or silver nanoparticles synthetized by green chemical reduction methodologies. Based on the results obtained, we found that silk fibroin from silk fibrous waste (SFw) favored the formation of gold (AuNPs-SFw) and silver (AgNPs-SFw) nanoparticles, acting as a reducing agent and surfactant, forming a micellar structure around the individual nanoparticle. Moreover, different electrospinning conditions influenced the morphological properties of the fibers, in the presence or absence of beads and the amount of sample collected. Furthermore, treated SFw electrospun membranes, functionalized with AuNPs-SFw or AgNPS-SFw, allowed the conduction of electrical stimuli, acting as stimulators and modulators of electric current.